AN ANALYSIS OF SWEARWORDS USED BY KING GEORGEVI IN KING’S SPEECH FILM (A PSYCHOSOCIAL STUDY) - Rullyanti, Merry; Khomairoh, Latifah (JURNAL LITERARY CRITICISM, 2018)
Swearing is an action doing by people contain with rude and harsh  words as the expression of stong emotion. This study aimed to describe the swearwords that used by King George VI in King’s Speech film. This is a historical film about King George VI and his daily life with many problems that make him take it especially in empire. The purposes of this study were: (1) to find out the kinds of swearwords that used by the King George VI (2) to know the factors that made him used swearwords (3) to analyze the situation when he used swearwords. The data were collected through the transcript of King’s Speech film. Spradley’s domain analysis, taxonomic analysis, componential analysis were used for analyzing the data in this research. The research finding showed that: (1) The highest swearwords that used by the King George VI in King’s Speech film are death term and the lowest are animal and mother in law term (2) The most factor that made him used swearwords are anger and then the lowest factor is humor. (3) Swearing as the way of the King to express his strong emotion by used rude words. And then, swearwords are only used by the King in certain situation and place such as in his physician’s building.                                            Keywords: Swearwords, King George VI, King’s Speech film.